The effect of stirring on the heterogeneous nucleation of water and of clathrates of tetrahydrofuran/water mixtures - Wilson, P.W.; Haymet, A.D.J. (Condensed Matter Physics, 2016)
The statistics of liquid-to-crystal nucleation are measured for both water and for clathrate-forming mixtures of tetrahydrofuran (THF) and water using an automatic lag time apparatus (ALTA). We measure the nucleation temperature using this apparatus in which a single sample is repeatedly cooled, nucleated and thawed. The effect of stirring on nucleation has been evaluated numerically and is discussed. We find that stirring of the solution makes no difference to the nucleation temperature of a given solution in a given tube.